Metabolic syndrome and associated factors among H. pylori-infected and negative controls in Northeast Ethiopia: a comparative cross-sectional study - Asmelash, Daniel; Nigatie, Marye; Melak, Tadele; Alemayehu, Ermiyas; Ashagre, Agenagnew; Worede, Abebaw (Frontiers in Endocrinology, 2024)
Abstract Background: The prevalence of metabolic syndrome (MetS) in patients infected with H pylori and the factors associated with it are not well understood. This study evaluates MetS and its associated factors among both H pylori-positive and H pylori-negative individuals in Northeast Ethiopia. Methods: A cross-sectional study was conducted between March 01/2022 to May 30/2022. A semi-structured questionnaire was used to collect data on sociodemographic, behavioral, and clinical variables. A total of 228 subjects were randomly selected. Blood and stool samples were collected from each subject to measure fasting blood glucose, lipid profiles, and to identify H. pylori infection. Data was entered into Epi. Data 3.1 and analyzed using SPSS version 25. Logistic regression analysis and the Mann-Whitney U-test were performed to determine associated factors and compare median and interquartile ranges. Results: Of the 228 participants, 114 were H. pylori positive, and 114 were H. pylori negative. Participants (50.9% female) ranged from in age from 18 to 63 years, with a median age of 31 (IQR: 22, 40) years. The overall prevalence of MetS among the participants was 23.2%. We found a statistically significant association between MetSand fasting blood glucose level (AOR: 15.965, 95% CI: 7.605-33.515, P<0.001). Furthermore, there was a statistically significant difference in the median serum levels of low-density lipoprotein cholesterol (p<0.001), triglycerides (P=0.036), systolic blood pressure (<0.001), and total cholesterol (P<0.001) between H. pylori-positive and H. pylori-negative participants. Conclusion: MetS was prevalent among study participants. There was also a statistically significant association between fasting blood sugar and MetS. In addition, systolic blood pressure, total cholesterol, triglycerides, and low-density lipoprotein levels were significantly different between H.pylori positive and negative individuals.